Thermodynamic Study of the Interaction of Benzylideneaniline with the Shift Reagent Cu (I) by U.V Spectroscopy - Sabeeh Jabur, Hasan; ., . (International Journal of Engineering and Technology, 2018)
The U.V. spectra of series of benzylidene (mono and di- substituted) anilines have been studied with the shift reagentcu (I). Addition of shift reagent causes a decrease in the absorption of A1& A2 bands which may be attributed to the complex formation with cu (I). The equilibrium constant for the process was calculated using the method of Hartman. The thermodynamic parameters(âˆ†G,âˆ†H,&âˆ†S)were obtained. Application of Skalski method show that the interaction with cu(fod)is 1:1.Â